Importance of time of concentration in run off peak flow estimation - Mamun, Abdullah Al; Salleh, Md Noor; Ibrahim, Saerahany Legori; Masbah, Dani Irwan; Daoud, Jamal Ibrahim; E.M. Yahya Khan, Nasehir Khan (2022)
Various methods and equations are used for hydrological calculations. Calculation of hydrograph peak flow is one of the common uses of such methods or equations. Peak flows and hydrographs can be calculated using several techniques. The manual calculation is one of the common ways to determine the peak flows for drainage design and river capacity of small catchments with a simple drainage network. In order to calculate the peak flow, the design rainfall duration has to be appropriate; which will reflect the critical storm duration. The critical storm duration on the other hand depends on the time of concentration (tc) of the catchment. However, most of the equations for tc available in the literature are empirical. At least 23 equations could be traced in various references, which consist of different geophysical and other hydrological parameters. This paper is intended to explain the importance of the proper use of tc to calculate peak runoff flow as accurately as possible. A review of the existing methods revealed inconsistencies among a few methods found in the literature. The correct value of the time of concentration (tc) is important for the application of the Rational Method, as the value of tc helps the designer to assume the storm duration critical to get the maximum peak flow value.